Safety on drilling and production oil platforms: application of lean six sigma methodology - Lima, Felipe de Oliveira; Teles, Claudia Rodrigues (Brazilian Journal of Production Engineering, 2022)
Lean thinking, or Lean Six Sigma, can be defined as a method or philosophy that uses tools and techniques to optimize, reduce the number of failures, and consequently increase the profitability of processes and products, always aiming for quality. The present research aims to apply the Lean Six Sigma methodology to analyze failure points in health and safety measures on offshore drilling and production platforms, and subsequently the application of the DMAIC cycle to those points to further decrease the occurrence of incidents/accidents on the platforms. The information for this study was collected via interviews with professionals in the offshore oil industry, who aimed to identify flaws in the processes related to safety on platforms from pre-embarkation to disembarkation. As results, it was possible to observe and propose improvements for five weak points, highlighting the low or zero cost for the measures presented. It was concluded that the application of the Lean Six Sigma methodology in platforms is of great value and brings reductions in risks related to occupational health and safety through improvements presented to the identified weak points.